Prevalence and associated factors of depressive symptoms among older adult diabetic patients in China: a nationally representative cross-sectional study - Huang, Huan; Wei, Wu-xiao; Huang, Tao; Wang, Feng; Zhang, Hai-tao (Frontiers in Psychology, 2025)
BackgroundDiabetes and depressive symptoms exhibit a high comorbidity in the older adult population, and their combined effects significantly reduce patients’ quality of life. This study aims to investigate the prevalence of depressive symptoms among older adults with diabetes in China and identify key associated factors, providing evidence-based insights for the development of targeted intervention strategies.MethodsThis study utilizes data from the 2015, 2018, and 2020 waves of the China Health and Retirement Longitudinal Study (CHARLS), including older adults aged 60 years and above who have been diagnosed with diabetes (n = 3,609). Depressive symptoms were assessed using the simplified version of the CES-D scale, a validated tool for measuring depressive symptoms, with a score of ≥10 indicating depressive symptoms. Univariate chi-square tests and logistic regression analysis were used to examine the factors associated with depressive symptoms, with statistical significance set at p < 0.05.ResultsThe overall prevalence of depressive symptoms among older adult diabetic patients in the sample was 38.6%. Univariate chi-square analysis revealed significant differences in variables including age (χ2 = 4.048, p = 0.044), gender (χ2 = 96.725, p < 0.001), educational level (χ2 = 110.545, p < 0.001), and sleep duration (χ2 = 161.070, p < 0.001) between the groups with and without depressive symptoms. Logistic regression analysis identified lower educational level (OR = 1.26, 95% CI: 1.03–1.55, p = 0.026), female sex (OR = 1.51, 95% CI: 1.22–1.88, p < 0.001), and shorter sleep duration (OR = 1.76, 95% CI: 1.41–2.18, p < 0.001) as independent risk factors for depressive symptoms. Furthermore, patients with comorbidities had a significantly increased risk of depressive symptoms (OR = 1.35, 95% CI: 1.06–1.72, p = 0.015).ConclusionThe high prevalence of depressive symptoms among older adult diabetic patients is significantly associated with sociodemographic, lifestyle, and health-related factors. Personalized psychological interventions should be prioritized for high-risk groups, including individuals with low education levels, women, those experiencing insufficient sleep, and those with multiple comorbidities, in order to enhance their quality of life and reduce social burdens.